Efficacy and cost‐effectiveness of voriconazole prophylaxis for prevention of invasive aspergillosis in high‐risk liver transplant recipients. Issue 2 (8th January 2016) - Balogh, Julius; Gordon Burroughs, Sherilyn; Boktour, Maha; Patel, Samir; Saharia, Ashish; Ochoa, Robert A.; McFadden, Robert; Victor, David W.; Ankoma‐Sey, Victor; Galati, Joseph; Monsour, Howard P.; Fainstein, Victor; et al.
Abstract : Aspergillus infection remains a significant and deadly complication after liver transplantation (LT). We sought to determine whether the antifungal prophylactic use of voriconazole reduces the incidence of invasive aspergillosis (IA) in high‐risk LT recipients without prohibitively increasing cost. During the study era (April 2008 to April 2014), 339 deceased donor LTs were performed. Of those patients, 174 high‐risk recipients were administered antifungal prophylaxis with voriconazole. The median biological Model for End‐Stage Liver Disease score at the time of LT was 33 (range, 18‐49) with 56% requiring continuous renal replacement therapy and 50% requiring ventilatory support immediately before transplantation. Diagnosis of IA was stratified as proven, probable, or possible according to previously published definitions. No IA was documented in patients receiving voriconazole prophylaxis. At 90 days after LT, the institutional cost of prophylaxis was $5324 or 5.6% of the predicted cost associated with post‐LT aspergillosis. There was no documentation of resistant strains isolated from any recipient who received voriconazole. In conclusion, these data suggest that voriconazole prophylaxis is safe, clinically effective, and cost‐effective in high‐risk LT recipients. Liver Transpl 22:163–170, 2016 . © 2015 AASLD.